If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 7 + -7 = -39 Reorder the terms: 7 + -7 + 2x = -39 Combine like terms: 7 + -7 = 0 0 + 2x = -39 2x = -39 Solving 2x = -39 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '2'. x = -19.5 Simplifying x = -19.5
| ln(x+4)+7=32 | | X^2+18x=-90 | | 13=x+17+x+10 | | t(n)=5*2n | | f(x)=2x^4+5x^2-12 | | .4x+.22=.06 | | 4y+5=3x+8-x | | 8(x+1)=6x-3 | | 15=14+x+x+15 | | 23=7x+5 | | 6x+13=4x+17 | | |10X+18|=|2X-8| | | x=5.5+3 | | -17m+9m=15-47 | | -4t^2-5t=-5t^3-4 | | 180=X+39+x+69 | | -5(r+2)=-78 | | -2+14=3b-4-2b | | m+1.2= | | 8x^2+2x-16=0 | | 2(7x-5)=39 | | [10X+18]=[2X-8] | | 4x=14+18 | | 3n+11=38 | | 5t^3-4t^2-5t+4= | | 6x-11=4x-9 | | -2x+9=-27 | | 2x=-27-3y | | 5B+5B-1=29 | | n-42=-15 | | 2x+1=3x-84 | | 11x+-6=2y |